151k views
0 votes
How to resolve this?
Thank you

How to resolve this? Thank you-example-1

1 Answer

4 votes


Serious stuff for July.


1. Sum of n even squares.


This is related to the sum of the squares of the integers. Lots of different proofs; how about we start from the difference of consecutive cubes.



\displaystyle S = \sum_(k=1)^n ((k+1)^3 - k^3)



\displaystyle S = \sum_(k=1)^n (3k^2 + 3k + 1)



\displaystyle S = 3 \sum k^2 + 3 \sum k + \sum 1



\displaystyle S = 3 \sum k^2 + 3n(n+1)/2 + n



\displaystyle \sum k^2 = \frac 1 3(S - (3/2) n(n+1) - n)


So all we need is S which is nicely telescoping:



S = (2^3 - 1^3) + (3^2 - 2^3) + (4^3 - 3^3) + ... + (n+1)^3-n^3



S = (n+1)^3 - 1



\displaystyle \sum k^2 = \frac 1 3((n+1)^3 - 1 - (3/2) n(n+1) - n)



\displaystyle \sum k^2 = \frac 1 6 n (n + 1) (2 n + 1)


We're interested in



\displaystyle \sum (2k)^2 = 4 \sum k^2 = \frac 2 3 n (n + 1) (2 n + 1) \quad\checkmark


That's just the first one. This is gonna be a long problem set.


2.



\displaystyle S = \sum_(j=1)^n (3j - 2)


That's a lot easier.



\displaystyle S = 3 \sum j - \sum 2



S = 3n(n+1)/2 - 2n



S = 3n(n+1)/2 - 2n



S = \frac 1 2 (3n^2 -n) \quad\checkmark


3.



\displaystyle \sum_(k=1)^n (5k-1) = 5 \sum k - \sum 1 = \frac 5 2 n(n+1)-n = \frac n 2(5n+3) \quad\checkmark


4.


Now it's getting interesting again.



\displaystyle S=\sum_(p=1)^n p(2^(p-1))


If I recall, the trick with these is turning them into double sums. Instead of multiplying by p, we'll add up p times.



\displaystyle S=\sum_(p=1)^n \sum_(q=1)^p 2^(p-1)


Let's just look at this for a minute as



\displaystyle S=\sum_(p=1)^n \sum_(q=1)^p f(p) = f(1) + f(2)+f(2) + f(3)+f(3)+f(3)+...


This is the tricky part; we want to exchange the order of the sums but we have the outer index p in the inner bound. When q is the outer sum it can't go to p so it must go to n:



\displaystyle S=\sum_(q=1)^n \sum_(p=?)^? f(p)


We have to fill in the question marks. We need
1f(2), 2f(2), ...nf(n) so we can see the bounds are:



\displaystyle S=\sum_(q=1)^n \sum_(p=q)^n f(p)


We can write the sum as the difference of two sums from 1.



\displaystyle S= \sum_(q=1)^n \left(\sum_(p=1)^n f(p) - \sum_(p=1)^(q-1) f(p) \right)


OK we substitute back in for f.



\displaystyle S=\sum_(q=1)^n \left( \sum_(p=1)^n 2^(p-1) - \sum_(p=1)^(q-1) 2^(p-1) \right)


That's two geometric series



\displaystyle S=\sum_(q=1)^n ( (1-2^n)/(1-2) - (1-2^(q-1))/(1-2) )



\displaystyle S=\sum_(q=1)^n ( 2^n - 2^(q-1))



\displaystyle S=\sum_(q=1)^n 2^n - \sum_(q=1)^n 2^(q-1)



\displaystyle S=n 2 ^n - (1-2^n)/(1-2)



\displaystyle S = (n-1)2^n + 1 \quad\checkmark


5.



\displaystyle S = \sum_(k=1)^n (1)/(k^2 + k)


Hmmm. Looks complicated but is that just a telescoper?



\displaystyle S = \sum_(k=1)^n (1)/(k(k+1))


It's not too hard to just guess the partial fractions:



\displaystyle S = \sum_(k=1)^n \left((1)/(k) - (1)/(k+1)\right)



\displaystyle S = (1)/(1) - (1)/(2) + (1)/(2) - (1)/(3) + ... + (1)/(n) - (1)/(n+1)



\displaystyle S = 1 - (1)/(n+1)



\displaystyle S = (n)/(n+1) \quad\checkmark


Phew. Tough problem set. It occurs to me now we could have done the hard ones by induction which probably would have been simpler.





User Neria Nachum
by
4.6k points